Comparison of upper extremity physical characteristics between adolescent competitive swimmers and nonoverhead athletes - Hibberd, E. E.; Laudner, K.; Berkoff, D. J.; Kucera, K. L.; Yu, B.; Myers, J. B. (Journal of Athletic Training, 2016)
Context: Alterations to upper extremity physical characteristics of competitive swimmers (posture, range of motion [ROM], and subacromial-space distance) are commonly attributed to cumulative training load during a swimmer's competitive career. However, this accepted clinical belief has not been established in the literature. It is important to understand whether alterations in posture and associated physical characteristics occur as a result of sport training or factors other than swimming participation to better understand injury risk and possible interventions.